Adult's Degenerative Scoliosis: Midterm Results of Dynamic Stabilization without Fusion in Elderly Patients—Is It Effective? - Mario Di Silvestre; Francesco Lolli; Tiziana Greggi; Francesco Vommaro; Andrea Baioni (Advances in Orthopedics)
Study Design. A retrospective study. Purpose. Posterolateral fusion with pedicle screw instrumentation used for degenerative lumbar scoliosis can lead to several complications. In elderly patients without sagittal imbalance, dynamic stabilization could represent an option to avoid these adverse events. Methods. 57 patients treated by dynamic stabilization without fusion were included. All patients had degenerative lumbar de novo scoliosis (average Cobb angle 17.2°), without sagittal imbalance, associated in 52 cases (91%) with vertebral canal stenosis and in 24 (42%) with degenerative spondylolisthesis. Nineteen patients (33%) had previously undergone lumbar spinal surgery. Results. At an average followup of 77 months, clinical results improved with statistical significance. Scoliosis Cobb angle was 17.2° (range, 12° to 38°) before surgery and 11.3° (range, 4° to 26°) at last follow-up. In the patients with associated spondylolisthesis, anterior vertebral translation was 19.5% (range, 12% to 27%) before surgery, 16.7% (range, 0% to 25%) after surgery, and 17.5% (range, 0% to 27%) at followup. Complications incidence was low (14%), and few patients required revision surgery (4%). Conclusions. In elderly patients with mild degenerative lumbar scoliosis without sagittal imbalance, pedicle screw-based dynamic stabilization is an effective option, with low complications incidence, granting curve stabilization during time and satisfying clinical results.